The Use of an Iliac Branch Device: Single-Center Study of Endovascular Preservation of Internal Iliac Artery Flow - Hyeseung Lee; Jeong-min Lee; Soongu Cho; JungUi Hong (Journal of the Korean Society of Radiology, 2023)
Purpose To determine the efficacy and safety of iliac branch device (IBD) implantation and to evaluate its limitations based on 7 years of experience in a single center. Materials and Methods This single-center study included patients with bilateral common iliac artery aneurysms (CIAAs). We investigated follow-up CT and reviewed the internal iliac artery (IIA) patency and complications related to IBD. A retrospective analysis was performed and the overall survival rate and freedom from reintervention rate were reported according to the Kaplan–Meier method. Results Of the 38 patients with CIAAs, only 10 (12 CIAAs) were suitable for IBD treatment. Five patients underwent unilateral IBD insertion with contralateral IIA embolization, and three (60%) showed claudication; however, symptoms resolved within 6 months. The 7-year freedom from IBD-related reintervention rate was 77.8%. No procedure-related deaths occurred. Conclusion IBD has good technical success and long-term patency rates; however, anatomical factors frequently limit its application, particularly in Asians. Additionally, unilateral IIA embolization showed relatively mild complications and a good prognosis; therefore, it can be performed safely for anatomically complex aortoiliac aneurysms.